Impact of prolonged one or more natural menstrual cycles on the outcomes of ovulation induction intrauterine artificial insemination pregnancy: a single-centre, retrospective study in China - Shuai Zhang; Han-Han Tang; Ming-Lian Zhou (BMJ Open)
Objectives We determined if the time interval between two ovulation induction intrauterine artificial insemination (IUI) treatment cycles should be extended by one or more natural menstrual cycles in patients undergoing successive cycles of ovulation stimulation, and whether this affects clinical pregnancy rate (CPR).Design This study was conducted on infertility patients treated under the ovulation induction programme IUI in a large reproductive centre in China. Study participants were assigned into continuous and discontinuous groups. Differences in baseline clinical pregnancy and abortion rates were compared between the groups. A multivariate logistic model was used to evaluate the effects of time interval on clinical pregnancy outcomes.Setting Reproductive Centre of Maternal and Child Health Hospital of Lianyungang city.Interventions None.Primary and secondary outcome measures The primary outcome measure was CPR, the secondary outcome measure was the abortion rate.Results A total of 550 IUI treatment cycles involving 275 couples were included in this study. Differences in CPR and abortion rate between the groups were not significant (20.5% vs 21.9% and 27.8% vs 22.0%, p≥0.05). Stratified analyses based on infertility factors did not reveal any significant differences in pregnancy and abortion rates between the groups (p≥0.05). Multivariate analysis showed that increased endometrial thickness correlates with CPR (OR 1.205, 95% CI 1.05 to 1.384, p=0.008). Compared with primary infertility, secondary infertility significantly correlated with improved CPR (OR 2.637, 95% CI 1.313 to 5.298, p=0.006). The effects of time interval between the first two ovulation induction IUI treatment cycles on clinical pregnancy were not significant (OR 1.007, 95% CI 0.513 to 1.974, p=0.985).Conclusions Longer time intervals between the first two ovulation induction IUI treatment cycles did not significantly improve CPR. Therefore, in the absence of clear clinical indications, it may not be necessary to deliberately prolong the interval between two ovulation induction IUI treatment cycles.